(3cjajI JSWjM GdcQI Ydi SWM GdCSWQdGHs - (3CMeO Hf eMeO Hf GdMSjf GdUZGfj (B( (3GdUGZGfj (B)(3, CHj MGeO GdCSWQdCHjs ((3GdehUd s)
(3ChdgG (B:s
(3bGd (B: (3Ef GdcQI JJSWM Ydi SWMjf CMOgeG SGcf hgh UajMI GdCSWQdGH hGdCNQ eJMQc hgh GdYfcHhJ s
(3BNQgG (B:s
(3hdYdg JgjC di HYO gPG GdacQ ai YchS gPg GdCTjGA GdJi YdeJgG Ydi CfgG UYHI LOkG Edi LedI gPG GdcJGH , hddg GdMeO hGdTcQ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B267(3C (B- (3U(B276(3Hs
(3Cdag ddedc TGgfTGg GdefUhQ YVO GdOhdI cJHJ Hbde eged GdfbW CMjGfkGs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs